THE EFFECT OF LEADERSHIP STYLE AND WORK PLANNING ON PUSKESMAS PERFORMANCE : (Study of ImplementationIndonesia Healthy Program in 2019) - Faisal Marzuki; Handono Mardiyanto; Diyah Yuli Sugiarti (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2018)
The purpose of this study was to find out whether there was effects to the leadership style and work planning towards the performance of puskesmas in the implementation Indonesia healthy program in 2019. This research was a quantitative study using survey methods. Herewith analyze and review the connection between each research variable. It is used analysis of Partial Least Squares (PLS) approachmentand a combination of quantitative and qualitative research. qualitative datathat obtained fromdirect interview with relevant officials inPuskesmas will be used to strengthen PLS analysis. the variables used in this study are: Puskesmas Performance (Y), Leadership Style (X1) and Work Planning (X2). the sample used in this study was 30 people out of 125 employees consisting of all Puskesmas units located in Sawangan Subdistrict, Depok city. The results of the study are leadership style influencing the performance of Puskesmas and work planning influences the performance of health centers.